EXPLORING STRATEGIES AND FACTORS INFLUENCING INFERENCE OF UNKNOWN WORDS: INSIGHTS FROM AN ELT LECTURER - Lachmy Narayana A/L Jogulu, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This study explores the word-meaning inferencing strategies used by non-native speakers to enhance their reading comprehension. Given the inconvenience of constantly consulting a dictionary, alternative strategies for inferring unknown words are essential. The study uses a semi-structured interview with an ESL lecturer to examine her views on the various lingual and non-lingual strategies that can be used to infer the meaning of unfamiliar words in L2. The interviewee also sheds light on several factors that affect word-meaning inferencing, including second language proficiency and text complexity. The findings suggest that multiple strategies can be employed to ensure accurate inferencing of unfamiliar words. This study provides an important contribution to the existing literature on word-meaning inferencing and emphasizes the need for further research in this area.